Divergent synthesis of meyers' lactams and medium lactams via cyclocondensation of γ-ylidene-butanolides with chiral amino alcohols - Sadanande, Megha V.; Sharma, Paridhi; Gonnade, Rajesh G.; Kontham, Ravindar (Journal of Organic Chemistry, 2026)
A novel methodology for constructing Meyers' lactams (pyrrolidino-oxazolidines), related to biologically potent natural and synthetic scaffolds, has been developed via an unprecedented tandem cyclocondensation of chiral 2-amino alcohols and gamma-ylidene-butanolides. The process proceeds through the initial formation of an ene-lactam intermediate, followed by a Bro/nsted acid (PPTS)-catalyzed ring closure. Under stoichiometric amounts of a Lewis acid (TiCl4), the same set of building blocks affords medium lactams featuring eight-membered ring systems with an exo-enol ether segment. This divergent synthetic strategy enables the efficient generation of a library of Meyers' lactams and medium lactams with good yields and diastereoselectivity.